2022
DOI: 10.1111/aji.13645
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IGFBP‐1, Fas, kallistatin, and P‐selectin as predictive biomarkers of histologic chorioamnionitis and associated intra‐amniotic infection in women with preterm labor

Abstract: Problem To determine whether altered levels of 13 plasma biomarkers, alone or in combination, could be independently associated with histologic chorioamnionitis (HCA) and microbial‐associated HCA (defined as the presence of HCA along with microbial invasion) in women with preterm labor (PTL). Methods of Study This was a retrospective cohort study involving 77 singleton pregnant women with PTL (23–34 gestational weeks) who delivered within 96 h of plasma and amniotic fluid (AF) sampling. DKK‐3, E‐selectin, Fas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…In particular, kallistatin acts as a negative acute phase protein that rapidly reduces its expression after lipopolysaccharide-induced inflammation in the liver, contributing to the decreased levels of kallistatin observed in the serum/plasma of patients with inflammation-related conditions, such as obesity, inflammatory bowel disease, and septic syndrome 46 , 48 , 49 . In line with inflammatory disease-related data 46 , 48 , 49 , our previous studies on pregnancies complicated by PTL or PPROM also showed that kallistatin levels are significantly decreased in the plasma of women with acute HCA or microbial-associated HCA 50 , 51 . Overall, the findings from the aforementioned studies 63 , 64 , as well as the inflammatory biological properties and expression profiles of kallistatin, are consistent with and support the herein described association between plasma kallistatin levels and MIAC, IAI, or SPTB risk outcome, given the reported relationships between these endpoints and acute HCA 4 , 52 , 53 .…”
Section: Discussionsupporting
confidence: 75%
“…In particular, kallistatin acts as a negative acute phase protein that rapidly reduces its expression after lipopolysaccharide-induced inflammation in the liver, contributing to the decreased levels of kallistatin observed in the serum/plasma of patients with inflammation-related conditions, such as obesity, inflammatory bowel disease, and septic syndrome 46 , 48 , 49 . In line with inflammatory disease-related data 46 , 48 , 49 , our previous studies on pregnancies complicated by PTL or PPROM also showed that kallistatin levels are significantly decreased in the plasma of women with acute HCA or microbial-associated HCA 50 , 51 . Overall, the findings from the aforementioned studies 63 , 64 , as well as the inflammatory biological properties and expression profiles of kallistatin, are consistent with and support the herein described association between plasma kallistatin levels and MIAC, IAI, or SPTB risk outcome, given the reported relationships between these endpoints and acute HCA 4 , 52 , 53 .…”
Section: Discussionsupporting
confidence: 75%
“…Our analysis identified a strong, negative correlation of AGP with plasma kallistatin, a circulating serine protease inhibitor with pleiotropic antioxidant, anti-inflammatory, and immunoregulatory functions affecting cardiovascular homeostasis [38]. A low plasma kallistatin level has recently been associated with an increased risk of chorioamnionitis in women experiencing preterm labor [39] and the preterm rupture of membranes [40], implicating its potential utility as a biomarker of chorionic inflammation.…”
Section: Discussionmentioning
confidence: 76%
“…The precision and accuracy of the nine ELISAs were validated for plasma samples before use through spike‐and‐recovery and linearity‐of‐dilution experiments, which revealed their good performance. These proteins were selected to be explored in the present study because (i) they were previously suggested to be useful blood biomarkers for the detection of histologic inflammation in the placenta; however, whether their altered expression in the plasma is associated with AF inflammation/infection and adverse neonatal outcomes in the context of PPROM remains unclear [22, 23]; (ii) they could have potential clinical significance in the maternal blood regarding the outcomes of interest herein investigated, considering previous proteomic profiling studies that suggested that they could be potential candidates biomarkers for MIAC, IAI, or preterm birth [18, 2426, 28, 32]; and because (iii) their related signaling pathways (such as inflammation/immune‐, cell adhesion, and ECM homeostasis [https://www.uniprot.org/]) are known to be involved in the pathogenesis of adverse pregnancy and neonatal outcomes [33–36].…”
Section: Methodsmentioning
confidence: 99%
“…Several inflammatory proteins, such as interleukin (IL)-6, low-affinity immunoglobulin gamma Fc region receptor III-A (FCGR3A), haptoglobin, lipopolysaccharide binding protein (LBP), matrix metalloproteinase (MMP)-9, and S100A8/A9, were previously reported as predictors of intraamniotic inflammation and/or microbial invasion of the amniotic cavity (IAI/MIAC) in the plasma of women with PPROM [5,[18][19][20]. However, in contrast to inflammatory plasma/serum markers, the role of adhesion-and extracellular matrix (ECM)-related biomarkers in the maternal plasma remains unclear with respect to IAI/MIAC and CNMM, despite the reported associations between their AF levels and in utero inflammation/infection, and between their plasma levels and placental inflammation [21][22][23]. Furthermore, the roles of other inflammatory proteins, including alpha-fetoprotein (AFP), C-X-C motif chemokine 14 (CXCL14), galectin-3-binding protein (Gal-3BP), kallistatin, and vitamin D-binding protein (VDBP),…”
Section: Introductionmentioning
confidence: 99%